OPTIMALISASI PENGEMBANGAN USAHATANI TANAMAN PADI DAN TERNAK SAPI SECARA TERPADU DI KABUPATEN MAJALENGKA - Davina Howara (Universitas Tadulako, 2011)
This research aimed at determining the optimal combination of integrated farming system inMajalengka in relation to land resource availability, production inputs, capital and credit. Data wasanalyzed using Linear Programming. The results of the research were (1) the optimal croppingpattern generated income more than IDR 1.34 billions, (2) with available credit and fertilizerassumption, the income obtained was more than IDR 1.61 billions, and (3) with availableproduction inputs and fertilizer assumption, the income received was more than IDR 1.64 billions.The study suggested that the credit policy increases land use and beef cattle number, thus increasefamers’ income.Key words : Integrated farming system, optimal solution, scenario and Majalengka.